Hoplerythrinus unitaeniatus (Characiformes, Erythrinidae): um complexo de espécies. Estudos citogenéticos clássicos e moleculares - Martinez, Juliana de Fatima (Universidade Federal de São Carlos, 2014)
Brazil has a large and dense hydrographic network distributed in eight major basins, with a great diversity of fish species. Erythrinidae is a small family of Characiformes, represented by only three genera: Erythrinus, Hoplerythrinus and Hoplias. Hoplerythrinus has only three species: H. cinereus (Gill, 1858), H. gronovii (Valenciennes, 1847) and H. unitaeniatus (Agassiz, 1829) and only the latter is found in Brazil, besides also occur in Central America and in several other countries in South America. H. cinereus and H. gronovii have a more restricted distribution and occur only in Trinidad and Tobago and Guyana, respectively. Only H. unitaeniatus has cytogenetic studies, proving to be a diverse chromosomally species, indicating it is a complex of species. In order to progress in the knowledge of the genome of H. unitaeniatus, this study aimed to characterize by conventional Giemsa staining, C-banding, impregnation with silver nitrate and fluorescence in situ hybridization (FISH) with probes of DNAr 18S and 5S, telomeric sequence (TTAGGG)n, histones (H3 and H4), and microsatellite (CA)15, (GA)15, (CAC)10, (GAG)10 and (GATA)n, populations of H. unitaeniatus from five hydrographic basin in Brazil (Amazon, Araguaia, Paraguay, Upper Parana and São Francisco). The diploid numbers found were 2n=48 (Paraguay and Upper Parana), 2n=50 (São Francisco) and 2n=52 (Amazon, Araguaia and São Francisco), besides the occurrence of natural hybrids with 2n=51 chromosomes in the São Francisco basin. The C-banding showed heterochromatic blocks located in the interstitial and pericentromeric position in most chromosomes, but some chromosomes also showed heterochromatic blocks in the centromeric and terminal position in all populations. The impregnation with silver nitrate revealed simple AgNORs for populations of the Amazon and Araguaia and multiple AgNORs for the populations of Paraguay, Upper Parana and São Francisco. FISH with 18S and 5S DNAr probes revealed several chromosomes carrying these cistron, besides the occurrence of synteny in all populations. Probes with telomeric sequence (TTAGGG)n detected sites only in the terminal vii portion of all chromosomes. A dispersed pattern was verified to H3 and H4 histones in the chromosomes and only for H4 was observed strongest blocks in the interstitial position. The chromosomal distribution of the microsatellites (CA)15, (GA)15, (CAC)10, (GAG)10 in the genome of H. unitaeniatus shown to be preferentially located in the terminal position of the chromosomes with some interstitial regions marked. The microsatellite (GATA)n shown dispersed in the chromosomes without preferential accumulation in a specific region of the chromosome in all populations analyzed. The data obtained in this study reinforce the hypothesis that H. unitaeniatus it is not a single species, but the specie complex H unitaeniatus.
Keywords: Citogenética de peixes; Erythrinidae; Diversidade cromossômica; Marcadores genéticos; Híbridos naturais; DNA ribossômico; CIENCIAS BIOLOGICAS::GENETICA